Zanzibar .. a historical study of the Omani presence in East Africa 1806-1856 (Journal of the College of Basic Education, 2022)
The Arab Gulf region has received the attention of researchers and cultural, political and research institutions.Many of these centers and institutions have begun working to develop and encourage scientific and political research. and historical studies that discuss the history of the Arabian Gulf.One of the most prominent results of these efforts was the care, collection and verification of manuscripts, and the emergence of manyObjective historical research in magazines and periodicals, and through this research lies the importance ofThe Arabian Gulf among researchers whose studies and research dealt with the history of this region and its people through